Regression Quadratic Method untuk Menganalisis Hubungan Sudut Kemiringan terhadap Radiasi dan Energi Panel Surya - Friska Ayu Fitrianti Sugiono; Dita Anies Munawwaroh; Ferriawan Yudhanto (Universitas Muhammadiyah Yogyakarta, 2023)
The potential of rooftop solar power plants at Semarang State Polytechnic Mechanical Engineering Workshop has been researched. This study discusses one of the factors that affect the radiation received and energy sent to the grid, namely the angle of inclination in the solar panels The average radiation data received by solar panels with variations in tilt angle between 0 to 30° and azimuth angles at 0° facing north and 180° facing south are simulated using Helioscope software. Based on the results of mathematical calculations, it is estimated that the relationship between the tilt angle of the solar panel and the radiation received and the energy sent to the grid will form a quadratic curve. From the results of data processing with the Regression Quadratic Method, it was obtained that the data match was 99.6%. The results of calculations using the quadratic equation show that the angle of inclination of the solar panels for installation of a rooftop PLTS in Machine Workshop Polines is 11° with a radiation of 1775.6 kWh/m2 and a energy production of 13575.9kWh.